Retrogradation of Truth and Omniscience - Ciro De Florio; Aldo Frigerio (Philosophies)
Todd and Rabern have argued that assuming future contingents are untrue, together with accepting the principle of the retrogradation of truth (<semantics>p→PF(p)</semantics>), implies that it is metaphysically impossible that an omniscient entity exists. Since the possibility of an omniscient being is a metaphyisical and theological thesis that should not depend on assumed temporal semantics, Todd and Rabern conclude that, if one wishes to maintain the untruth of future contingents, one must reject the principle of the retrogradation of truth. This paper aims to show that Todd and Rabern’s argument fails. We present a temporal semantics in which future contingents are untrue, the principle of the retrogradation of truth is valid, and the potential existence of an omniscient and temporal being is preserved.